THE PERCEPTION OF GENDER ROLES AND ITS IMPLICATION FOR SPOUSAL VIOLENCE IN KADUNA METROPOLIS, KADUNA STATE, NIGERIA - Mudiare, Patience E. Ukiri (European Scientific Journal, ESJ, 2013)
﻿﻿The paper examines the socio-cultural bases of spousal violence in Kaduna Metropolis. It x-rays the perception of gender roles and the socio-cultural causes of spousal violence within the generic concept of gender violence. Given the dearth of data and the lack of systematic documentation of spousal violence, this study attempts to fill the gap by providing a gender sensitive data through its gender disaggregated analysis. The findings of this study were derived from a survey of 590 respondents, 48.9 % (290) females and 51.1% (300) males using the multi-stage cluster sampling technique as well as qualitative data from Focus Group Discussions and In-depth interviews with key informants in the community. The findings reveal that most people still subscribe to the traditional gender roles though submissiveness of women is increasingly being challenged. Moreover, while violence against women is condoned, violence against men by women is unacceptable. Women therefore retaliate through passive resistance in the form of deliberate sluggishness, refusal to serve food and sexual neglect. Insubordination of women and sex related problem were perceived as causes of violence against women while female violence was attributed to aggressiveness on the part of husbands, sex related problems, neglect of the provider role and interference from mothers in-law. The paper concludes that much of the violence that men and women experience is borne out of the social and cultural prescriptions which often are skewed in favour of men and in line with the findings, appropriate recommendations are highlighted. In particular, in view of the important role religion plays in Nigeria, religious leaders should be involved in changing people’s perception on gender roles and attitudes to spousal violence.